2010
DOI: 10.1002/ptr.2868
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity and Mode of Action of Propolis Extracts and Selected Compounds

Abstract: Aqueous and ethanol extracts of propolis were analysed phytochemically and examined for their antiviral activity in vitro. Different polyphenols, flavonoids and phenylcarboxylic acids were identified as major constituents. The antiviral effect of propolis extracts and selected constituents, e.g. caffeic acid (1), p-coumaric acid (2), benzoic acid (3), galangin (4), pinocembrin (5) and chrysin (6) against herpes simplex virus type 1 (HSV-1) was analysed in cell culture. The 50% inhibitory concentration (IC(50))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
140
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(153 citation statements)
references
References 32 publications
7
140
0
6
Order By: Relevance
“…Chlorogenic acid and its related compounds are abundant plant polyphenols that have anti HSV-1 activity (Chiang et al, 2002;Wang et al, 2009;Nolkemper et al, 2010). In the same way, the anti-HSV activity of naturally occurring flavonoids has also been described (Lyu et al, 2005;Schnitzler et al, 2010). Therefore, our findings suggest that at least part of the anti HSV-1 effects of the RCE40 extract might be attributable to its phenolic composition.…”
Section: Antiviral Activitysupporting
confidence: 71%
“…Chlorogenic acid and its related compounds are abundant plant polyphenols that have anti HSV-1 activity (Chiang et al, 2002;Wang et al, 2009;Nolkemper et al, 2010). In the same way, the anti-HSV activity of naturally occurring flavonoids has also been described (Lyu et al, 2005;Schnitzler et al, 2010). Therefore, our findings suggest that at least part of the anti HSV-1 effects of the RCE40 extract might be attributable to its phenolic composition.…”
Section: Antiviral Activitysupporting
confidence: 71%
“…The propolis treatment did not appear to have antiviral activity (except for the marginal activity against BQCV only, in May 2014), although it has been reported that some viruses are more susceptible to propolis than others in vitro (Amoros et al, 1992;Kujumgiev et al, 1999). The antiviral activity of propolis against human viruses is well documented in human cell culture (Amoros et al, 1992;Gekker et al, 2005;Kujumgiev et al, 1999;Schnitzler et al, 2010). Viruses are obligate intracellular parasites and they must enter host cells in order to live and reproduce.…”
Section: Discussionmentioning
confidence: 99%
“…Chrysin (5,7-dihydroxyflavone) is a natural flavonoid presented in many plant extracts, including blue passion flower (Passiflora caerulea), honey and propolis (10). A number of studies have shown that chrysin has multiple biological activities, such as antiinflammation, antioxidation and anticancer effects (11)(12)(13). Chrysin has been reported to induce apoptosis in a panel of cancer cell lines, including HeLa cervical cancer cells, U937, HL-60 and L1210 leukemia cells (14).…”
Section: Introductionmentioning
confidence: 99%